Determining factors in process of socio-technical adequacy of renewable energy in Andean Communities of Salta, Argentina - Escalante, Karina Natalia (2013)
The use of renewable energy presents a great potential to solve energy problems in remote communities. However, in populations of the northwestern of Argentina, there are a large number of abandoned devices. This situation motivated the research on the processes of 'technology transfer', in order to make theoretical and methodological contributions to help to improve them. The development of this work was based on the analysis of case studies in the Andean communities of Cabrería, San Juan and Las Capillas (Province of Salta, Argentina) where solar water heaters were 'transferred'. The main results presented in this paper are the identification, assessment and analysis of factors and sub-factors that conditions the analyzed processes. There were identified the following determining factors: solar technology, community participation, involvement of technicians, inter-institutional coordination, logistics and monitoring of the project, and structure of the community. The analysis of interaction showed a strong interdependence among factors, in this manner; the way in which a factor is applied directly influences the development of other factors. Finally, it should be noted that although the analyzed experiences have much in common, each situation of socio-technical adequacy is particular and therefore it requires the opening-up of researchers and technicians to adapt technologies and methodological approaches of these processes.